Low‐cost fabrication of polymer substrate‐based piezoelectric microgenerator with PPE, IDE and ME - S.S. Balpande; M.L. Bhaiyya; R.S. Pande (Electronics Letters)
Piezoelectric microgenerator is an incredible method which makes a self‐powered wireless sensor node. It is a process of converting ambient energy into electrical energy. Flexible microgenerator goes well with many natural curved, rough and arbitrary surfaces such as human bodies, organisms, clothes and structure surfaces. Zinc oxide and polymer have been used as piezoelectric material and substrate, respectively, for biocompatible device. The harmonic analysis was carried out using finite element method (FEM) tool to examine the effect of the electrodes on the output voltage. Microgenerators with different electrodes were fabricated and examined their performance. Traditional parallel plate metal electrodes (PPEs) are prone to cracks and internal defects on bending or stretching, thus mesh electrodes (MEs) has been proposed. Copper MEs based microgenerator has performed at par. Open‐circuit electric potential of 2.8 VPEAK, 435 mVRMS for ME against electric potential of 2.3 VPEAK, 430 mVRMS and 0.9 V, 340 VPEAK, 40 mVRMS for interdigitated electrodes (IDEs) and PPE, respectively, were recorded. Design, fabrication, electrical characterisation and comparative evaluation of microgenerator with three different electrodes are presented.